Mengurai Benang Kusut: Strategi, Metode, Teknik Dan Pendekatan Dalam Pembelajaran - Suryati, Suryati (Program Pascasarjana IAIN Langsa, 2023)
The spirit of education is learning. To make the spirit good, the learning process must be good and optimal, one of which is engineering very well and applying appropriate and good teaching materials. Within the scope of the teaching and learning process, there are many terms that we often hear, such as strategies, techniques, models, methods, approaches, and others. These things will describe the situation and the teaching and learning process carried out by the teacher for his students. But in fact, there are often mistakes in the meaning of these terms. Educators also often generalize the intent and purpose of these terms. In practice, its use also often runs away from the actual rules. In order to clarify and detail the characteristics of each of these terms, they really need to be discussed conceptually. This really needs to be done so that deviations and doubts in the meaning of each do not happen again, especially among educators. This paper will discuss in detail the meaning of approaches, methods, models, strategies, and techniques in learning because these five terms are often used in the teaching and learning process. To obtain the data in this paper using qualitative methods with a literature review, It will dig up information from sources such as books, journals, articles, and others.